Dwa egzempla cysterskie z Liber Visionum et Miraculorum Clareva llensium Herberta z Clairvaux jako domniemane źródła do rekonstrukcji wierzeń słowiańskich. Studium historiograficzne - Sołtysiak, Alicja (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
In her work, the author addresses two exempla from Liber Visionum et Miraculorum Clarevallensium by Herbert of Clairvaux, in historiography treated as sources for the reconstruction of Slavic beliefs. In the first subchapter, she characterises the Cistercian exemplum genre and explains its specificity. She focuses on the credibility of the stories conveyed in them. The next section presents the most important facts from Herbert’s life, as well as an outline of the most significant textual and dating issues concerning his book. It then provides an overview of the content of the two exempla and points out the difficulties with the titles as they vary from one manuscript to another. The most important part of the work is the subsection devoted to historiography where the author analyses the problems resulting from some scholars ignoring the stages of historical research, namely heuristics, criticism and reconstruction. This allows her to document, among other things, how unreliable research, ignorance of Latin, and disregard of interpretatio Christiana affect the conclusions drawn by some authors dealing with the two exempla. In conclusion, the author concludes that the exempla are of very little value for the reconstruction of pre-Christian Slavic beliefs and rituals. At the same time, she puts forward research proposals for the broadest possible analysis of the so-called Danish-Slavic cycle from Herbert’s work.